Survival outcomes and prognostic factors in surgically treated adult pilocytic astrocytomas - Park, Sanghyeok; Seo, Jung Han; Song, Sang Woo; Cho, Young Hyun; Hong, Chang-Ki; Kim, Jeong Hoon; Kim, Ho Sung; Park, Ji Eun; Nam, Soo Jung; Kim, Young-Hoon (Frontiers in Oncology, 2025)
PurposePilocytic astrocytomas (PA) in adult patients are rare and the efficacy of postoperative adjuvant treatments remains unclear. This study aims to investigate the survival outcome and prognostic factors in surgically treated adult PA.MethodsA total of 90 consecutive adult patients with newly diagnosed PA were enrolled. Among the patients, 47 (52%) were male, with a median age of 28 years (18–70 years). Preoperative neurological deficits were observed in 43 (48%) patients. The most common tumor locations were cerebellar and cerebral hemispheres (28% and 27%, respectively), while 23% of tumors were located in deeper brain structures. The median follow-up duration was 88months (12–304 months).ResultsGross total removal (GTR) was achieved in 55 (61%) patients. At the final follow-up, 12 (13%) patients had died, and 23 (26%) experienced disease progression. The 1, 2, and 5-year overall survival (OS) rates were 93%, 91%, and 87%, respectively, while the progression-free survival (PFS) rates were 88%, 80%, and 77%, respectively. The recurrence rate in patients who underwent GTR was 11%, compared with 53% and 45% in those without GTR, with or without adjuvant treatments, respectively. The tumors in the deeper brain locations had significantly lower GTR rates (14%) compared with other locations (75%; p < 0.001). Multivariate analysis identified the absence of preoperative neurological deficits (p = 0.048; HR = 2.878), not deeper tumor location (p = 0.017; HR = 3.471) and GTR (p = 0.007; HR = 3.884) as significant factors for improved PFS.ConclusionAdult PA exhibited more aggressive behavior compared with pediatric PA. These aggressive behaviors including preoperative neurological deficits, deeper tumor location, and lower GTR rates were significantly associated with poor prognosis.